Cyanobacteria Biorefinery - Production of poly(3-hydroxybutyrate) with Synechocystis salina and utilisation of residual biomass - Meixner, K; Kovalcik, A; Sykacek, E; Gruber-Brunhumer, M; Zeilinger, W; Markl, K; Haas, C; Fritz, I; Mundigler, N; Stelzer, F; Neureiter, M; Fuchs, W; et al. (Journal of biotechnology, 2018)
This study evaluates a biorefinery concept for producing poly(3-hydroxybutyrate) (PHB) with the cyanobacterial strain Synechocystis salina. Due to this reason, pigment extraction and cell disruption were investigated as pre-treatment steps for the harvested cyanobacterial biomass. The results demonstrated that at least pigment removal was necessary to obtain PHB with processable quality (weight average molecular weight: 569-988kgmol-1, melting temperature: 177-182°C), which was comparable to heterotrophically produced PHB. The removed pigments could be utilised as additional by-products (chlorophylls 0.27-1.98mgg-1 TS, carotenoids 0.21-1.51mgg-1 TS, phycocyanin 0-127mgg-1 TS), whose concentration depended on the used nutrient source. Since the residual biomass still contained proteins (242mgg-1 TS), carbohydrates (6.1mgg-1 TS) and lipids (14mgg-1 TS), it could be used as animal feed or converted to biomethane (348 mn3 t-1VS) and fertiliser. The obtained results indicate that the combination of photoautotrophic PHB production with pigment extraction and utilisation of residual biomass offer the highest potential, since it contributes to decrease the environmental footprint of the process and because biomass could be used in a cascading way and the nutrient cycle could be closed.
Keywords: Polyesters; metabolismus lipidů; hydroxybutyráty; Lipid Metabolism; Synechocystis; Pigments, Biological; Biomass; polyestery; Cupriavidus necator; biomasa; Carbohydrate Metabolism; Hydroxybutyrates; metabolismus sacharidů; biologické pigmenty